Effects of hybrid and maturity at harvest on agronomic performance of corn for silage - Suazo, R.; Sonon, R.N.; Pfaff, L.; Dickerson, J.T.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve, commercial, corn hybrids were grown under irrigated conditions in 1990 and evaluated for agronomic and silage characteristics at three stages of maturities (1/2 milk line, black layer, and 7 days post-black layer). Time to mid-anthesis and mid-silk ranged from 62 to 68 and 65 to 70 days, respectively, and plant height ranged from 78 to 98 inches. Whole-plant dry matter (DM) content and whole-plant DM and grain yields for the 12 hybrids ranged from 23.6 to 53.7 %, 6.1 to 9.6 tons of DM per acre, and 60 to 170 bushels per acre, respectively, over the three maturities. Whole-plant DM content and grain yield increased (P<.001) with advancing maturity, whereas whole-plant DM yield peaked at the second maturity. These initial results indicate that hybrid and stage of maturity affect the agronomic characteristics of corn grown for silage.
Keywords: Beef; Corn; Hybrid; Maturity; Silage